2014
DOI: 10.1016/j.parint.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Short-term protection conferred by Leishvacin® against experimental Leishmania amazonensis infection in C57BL/6 mice

Abstract: To date, there is no vaccine available against human leishmaniasis. Although some vaccination protocols can induce immunity in murine models, they fail to induce protection in humans. The reasons for that remain unclear. The aim of the present study was to characterize the changes in the pattern of the immune response during subcutaneous vaccination with Leishvacin® in mice. We also investigated whether IFN-γ and nitric oxide synthase are indispensable for the protection elicited by the vaccine. C57BL/6 WT vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…We demonstrated the partial involvement of TLR9 in LaAg vaccine in the lesion control and parasite load (Figs 10 and 11). Although some studies investigate the profile of the immune response during vaccination against leishmaniasis, this is mainly focused on IFN-γ and iNOS [49], and few studies investigate the participation of receptors, specially TLR9, in vaccination mechanisms against leishmaniasis. From what we know at present, this is the first report that associates the importance of TLR9 receptor in LaAg vaccine efficacy against leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated the partial involvement of TLR9 in LaAg vaccine in the lesion control and parasite load (Figs 10 and 11). Although some studies investigate the profile of the immune response during vaccination against leishmaniasis, this is mainly focused on IFN-γ and iNOS [49], and few studies investigate the participation of receptors, specially TLR9, in vaccination mechanisms against leishmaniasis. From what we know at present, this is the first report that associates the importance of TLR9 receptor in LaAg vaccine efficacy against leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously argued the importance of the early response to Leishmania in subsequent infection outcome and vaccine efficacy (Hohman and Peters, 2019). The dual role played by IFNg may explain why vaccination strategies that induce highly polarized Th1-IFN-g-mediated immunity against phagosomal pathogens do not necessarily induce protection, potentially due to enhanced and counter-productive recruitment of permissive monocytic host cells and/or IL-10 production (Carneiro et al, 2014;Darrah et al, 2019;Peters et al, 2012).…”
Section: Llmentioning
confidence: 99%
“…One previous study designed to evaluate the quality of the Th1 response induced by L. amazonensis and L. braziliensis promastigotes extracts in PBMC from healed CL patients demonstrated that L. amazonensis response is associated with a low contribution of multifunctional T cells and a high number of IFN-γ single-positive effector cells, while L. braziliensis induces a Th1 response with high proportion of multifunctional T cells and low proportion of IFN-γ single-positive cells ( 39 ). As IFN-γ single-positive CD4+ T cells are short-lived, this can offer a possible explanation for the contrasting results observed in prophylaxis and immunotherapy studies with L. amazonensis whole-cell extract vaccine (Leishvacin ® ) ( 40 , 56 58 ). The substantial amount of IFN-γ single-positive effector CD4+ T cells induced by this antigen may not be sufficient to induce long-term and good-quality protection against infection, but could be effective when a rapid and transient Th1 response is needed, as in the case of immunotherapeutic interventions.…”
Section: Amazonensis Versus L Braziliensis mentioning
confidence: 99%